Acrylic-Casein Latexes with Potential Application as Adhesives - Aguzin, Ana (2020)
The replacement of monomers derived from petrochemical sources by biopolymers like proteins, together with the development of new materials with improved properties, have an increasing importance in industrial applications. In this context, the synthesis of acrylic-casein hybrid latexes was investigated through a low environmental impact strategy, such as the surfactant-free emulsion polymerization, with the aim of producing new industrial adhesives. Different aspects of the synthesis of hybrid latexes were addressed, such us i) the use of variable content of protein; ii) the control of grafting degree between polymers, using native casein (without chemical modification) or functionalized casein, and iii) the employment of a chain transfer agent to reduce molecular weights of the acrylic polymer. The effect of the analyzed variables on the polymerization kinetics, the degree of compatibility between polymers, and the application properties of the produced latexes as adhesives were investigated.